How prior experience and self-efficacy shape graduate student perceptions of an online learning environment in computing. Issue 4 (2nd October 2019) - Kreth, Quintin; Spirou, Mary Eve; Budenstein, Sarabeth; Melkers, Julia
ABSTRACT: Background & Context : As graduate programs in computing expand to online environments, existing research is limited in its ability to inform both practical and theoretical understandings of the factors influencing student success. Objective : We explore student perceptions of their learning environment at the understudied intersection of online graduate education, STEM, and adult learning. We focus on how students' human capital influences self-efficacy and how self-efficacy shapes perceptions of the learning environment. Method : We conduct a survey of students in a large, online MS program in computer science, then examine those findings using descriptive statistics and OLS. Findings : Findings indicate gender variation in both learning and computing self-efficacy and in how positively students perceive the online learning environment. Students with prior online education experiences have lower learning self-efficacy. Implications : Low learning self-efficacy is one potential mechanism for why online students struggle to succeed, even in specialized fields. Adapting support structures, advising, and admissions may help address these challenges.